COMMUNICATION STRATEGY OF THE NORTH SUMATRA KPOTI ORGANIZATION IN REVITALIZING TRADITIONAL SPORTS AMIDST THE CURRENT OF MODERNIZATION - Akhsanul Hidayat; Yusniah Yusniah (Journal Analytica Islamica, 2025)
This study aims to analyze the organizational communication strategies of KPOTI North Sumatra in revitalizing traditional sports amid the currents of modernization. Using a descriptive qualitative approach and a single case study design, data were collected through in-depth interviews, participatory observation, and media documentation. The data analysis followed the Miles, Huberman, and Salda